UPAYA PENINGKATAN KEMAMPUAN PERAWAT DALAM IMPLEMENTASI MODEL ASUHAN KEPERAWATAN PROFESIONAL (MAKP) DI RUANG RAWAT INAP RUMAH SAKIT UNIVERSITAS BRAWIJAYA MALANG - Ike Nesdia Rahmawati; Ahsan Ahsan; Kuswantoro Rusca Putra; Linda Wieke Noviyanti; Evi Harwiati Ningrum (Caring : Jurnal Pengabdian Masyarakat, 2021)
AbstractThe increasing public demand for quality nursing services require Nurse managers to improve the quality of nursing services. The professional Model of Nursing Care or Model Asuhan Keperawatan Profesional (MAKP) is a strategy to improve the quality of nursing care. Therefore, nursing services become more structured, organized, professional and comprehensive. The implementation of this community service activity consists of three stages, namely the MAKP training stage for nurses, the MAKP implementation assistance stage in inpatient wards, and the evaluation of MAKP implementation. The results of this community services were shown by The increase of nurses’ knowledge by 84.2% before and after training. As many as 79.4% of participants were active during the discussion of MAKP. The results of the evaluation of MAKP implementation assistance were 82.5% rate of Standard Operational Procedure (SOP) on the these following activities: handover, pre-conference, post-conference, discharge planning, and nursing rounds. MAKP training is able to increase the effectiveness of nursing services in the hospital. It is highly expected that training to improve other nurses' abilities can continue to be carried out as a form of collaboration between nurse academics and practitioners. This community service is also expected to bridge the implementation of nursing theories and concepts in clinical settings.AbstrakPermintaan masyarakat terhadap pelayanan keperawatan yang bermutu yang semakin meningkat menuntut pembenahan dalam manajemen keperawatan untuk peningkatan mutu layanan keperawatan. Model Asuhan Keperawatan Profesional (MAKP) merupakan strategi peningkatan mutu asuhan keperawatan. Sehingga pelayanan keperawatan menjadi lebih terstruktur, terorganisir, profesional dan komprehensif. Pelaksanaan kegiatan pengabdian masyarakat ini terdiri dari tiga tahap yaitu tahap pelatihan MAKP bagi perawat, tahap pendampingan implementasi MAKP di ruang rawat, dan evaluasi implementasi MAKP. Hasil evaluasi kegiatan ini pengetahuan perawat yang meningkat adalah sebesar 84,2% dari sebelum dan sesudah pelatihan. Sebanyak 79,4% peserta aktif dalam diskusi. Hasil evaluasi pendampingan implementasi MAKP didapatkan 82,5% sesuai dengan SOP meliputi operan, preconference, postconference, discharge planning, dan ronde keperawatan. Pelatihan MAKP mampu meningkatkan efektifitas pelakasanaan pelayanan keperawatan di rumah sakit. Diharapkan pelatihan peningkatan kemampuan perawat yang lain dapat terus dilaksanakan sebagai bentuk Kerjasama antara perawat akademisi dan praktisi. Kegiatan pengabdian masyarakat ini juga diharapkan menjembatani implementasi teori dan konsep keperawatan secara teknis di layanan Kesehatan.